2021
DOI: 10.3390/vaccines9091025
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Vaccines against Group A Streptococcus Can Effectively Target Broad Disease Presentations

Abstract: Group A Streptococcus (GAS) is an important global human pathogen, with a wide range of disease presentations, from mild mucosal infections like pharyngitis to invasive diseases such as toxic shock syndrome. The effect on health and mortality from GAS infections is substantial worldwide, particularly from autoimmune sequelae-like rheumatic heart disease (RHD), and there is currently no licenced vaccine. We investigated protein antigens targeting a broad range of GAS disease presentations as vaccine components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…We also demonstrate that asymptomatic S. pyogenes colonization leads to seroconversion to several antigens representative of different stages in S. pyogenes infection, with differences in antibody magnitude across the different targets measured[14]. Higher serological responses to S. pyogenes antigens were observed in children colonized at any timepoint in our study compared to non-colonized controls.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We also demonstrate that asymptomatic S. pyogenes colonization leads to seroconversion to several antigens representative of different stages in S. pyogenes infection, with differences in antibody magnitude across the different targets measured[14]. Higher serological responses to S. pyogenes antigens were observed in children colonized at any timepoint in our study compared to non-colonized controls.…”
Section: Discussionsupporting
confidence: 57%
“…The data provide further evidence that the impact of LAIV on colonization with potentially pathogenic bacteria is only modest and supports the wider rollout of LAIV to reduce influenza disease and its complications in LMICs. We also demonstrate that asymptomatic S. pyogenes colonization leads to seroconversion to several antigens representative of different stages in S. pyogenes infection, with differences in antibody magnitude across the different targets measured [14]. Higher serological responses to S. pyogenes antigens were observed in children colonized at any timepoint in our study compared to non-colonized controls.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…All tested dilutions from Day 70 bleed showed that the IdeS protease activity was neutralised to >70% (Fig. 5C) and exceeded the neutralisation ability of a positive control sample from previous IdeS immunisation [64]. The data suggests that IdeS-RhaPS could provide a dual-hit vaccine candidate, targeting the Strep A surface carbohydrate and the secreted protease IdeS.…”
Section: Evaluation Of Rhaps Glycoconjugates For Their Immunogenicitymentioning
confidence: 84%